The relationship of vocabulary and reading comprehension in the writing skills descriptive text reviewed gender - Silvana Nurdiani; Syahrul. R; Abdurahman Abdurahman (Fakultas Ilmu Pendidikan UNP)
This research to test the hypothesis in Contribution of vocabulary and reading comprehension on the writing skills description text reviewed gender, in a sample of 105 (52 males and 53 females) Junior high school students selected at random sampling. The data these research data were collected with multiple choice tests and performance tests, of this analyzed using regression technique Statistical analysis revealed that the contribution of vocabulary knowledge and reading comprehension in the main and interaction effects. Results of correlational analysis suggest that vocabulary and reading comprehension related significantly to the writing skills description text.